Industrial relations transformation PAL's flight to industrial peace and profitability - SZal, Regina C. Salas- (2006)
This study described, explored and outlined the process and context of change and transformation of industrial relations at the Philippine Airlines (PAL)-the national flag carrier of the Philippines-by taking a critical and closer look into the labor-management relations between PAL and PAL Employees Association (PALEA) during the period from 1998 to 2005. The researcher identified the factors that caused conflict and the circumstances that led to the transformation of the labor-management relationship, the steps taken by labor and management for the airline's survival, profitability, productivity and competitiveness; and the efforts to maintain employment security, decent working conditions and fringe benefits. The findings revealed how global market and economic environmental pressures prompted labor and management to modify traditional collective bargaining practices and to a shift in focus by putting a premium on industrial peace, flexibility, adaptability and increased union participation. The research pinpointed the major change from the traditional industrial relations system that was tripartite and adversarial in nature into a transformational and innovative IR system. The traditional pattern featured a confrontational, conflict-based, antagonistic and legalistic labor- management relationship while the transformational industrial system was characterized as participatory, cooperative and harmonious with increasing focus on union participation and maintenance of industrial peace. The researcher discovered that there were significant changes in both union and management strategies, bargaining structures and processes that resulted to the absence of serious labor disputes and minimal of government intervention. The impact of the continuing transformation of industrial relations at PAL was industrial peace and increased productivity and profitability.